Simulated Explanation of Brain Death Training Improves Resident Communication Competencies, Leading to Optimal Family Donation Conversation by OPO Staff. (August 2017) - O'Shaughnessy, Gweneth; Goldberg, Amy; Reynolds, Andrea; West, Sharon; Schimpf, Christopher; Hasz, Richard; Nathan, Howard
Abstract : Introduction: The Partnership for Organ Donation and Harvard School of Public Health have shown a clear link to public understanding of brain death and authorization for donation. The foundation of practice for many organ procurement organizations (OPOs) is rooted in education of and partnership with medical professionals who refer neurologically injured patients to the OPO and explain brain death to families. This study describes the results of one OPO's experience with 'Explaining Brain Death' training for residents. Methods: The OPO in collaboration with the Trauma Director at a large urban trauma/transplant center created a simulated training program to equip residents with the knowledge, skills, and confidence required to have these difficult conversations about brain death. The training included a didactic session with a focus on the optimal donation process and simulated role-play scenarios where residents could practice their skills. The OPO served as faculty and coached the residents; providing immediate feedback based on a 12-point check list. 722 residents from ten medical academic centers have been trained in 82 sessions held during 2009 and 2016. 71% were in their first year of residency. 32% indicated they learned how to explain brain death to families in medical school, while 42% said they were never taught how to explain brain death. Knowledge, skill, and confidence were assessed pre and post training. Results: Pre training data showed that only 25% of residents were comfortable discussing brain death; this improved to 88% post training. When asked if it should be standard protocol to refer a neurologically injured patient to the OPO prior to brain death testing, 59% initially agreed; following the training, this improved to 93%. Conclusion: Trained residents demonstrated and reported an increased level of knowledge, skill, and confidence in their ability to discuss brain death. It is appropriate and beneficial for OPOs to partner with hospitals to develop such resident training programs because previous research has demonstrated an empirical link between family understanding of brain death and authorization for organ donation. Family understanding and acceptance of death sets the stage for an optimal OPO approach to family conversations regarding donation. Future research is required to evaluate the skills of trained versus non-trained residents who explain brain death to families in addition to donation outcomes when these families are approached for authorization for organ donation. Figure. No caption available.